Contamination by heavy metals and petroleum hydrocarbons: a threat to mangroves - Alencar, Thaís dos Santos (2016)
The mangrove ecosystem is one of the most productive ecosystems on the planet with relevant ecological importance. It offers several services such as protection of the coastal region, immobilization of contaminants, as it is a food source and refuge for various organisms. However, mangroves are threatened by human activities. Oil spills in areas close to mangroves, for example, are potential sources for the entry of contaminants such as heavy metals and hydrocarbons. Among other sources of threat, we list industrial waste and sewage, mining and fertilizer use. When they reach the mangroves, these contaminants may cause several negative effects and affect its balance.